WHEN DID ZAMBIA START GOING GREEN? ASSESSING THE ALLUSION TO AND INCLUSION OF CLIMATE CHANGE AND INCIDENTAL PHENOMENON IN DEVELOPMENT PLANNING POLICY FROM 1964 TO 2021 - Zulu, Kangacepe; Simenti-Phiri, Easton (Advances in Social Sciences Research Journal, 2022)
Combining a three-pronged document review approach with semi-structured and in-depth interviews, this study provides a critical assessment of the emergence and progression of inclusion of climate change and incidental phenomenon in Zambia’s development policy. Specifically, the study seeks to trace these issues within each and every National Development Plan (NDP) published by the Government since Zambia’s independence in 1964. Results, synthesized from the different data sources, show that NDPs have progressively incorporated environmental issues from as early as the 1960s, with more recent consolidation of climate change and its increased inclusion beginning in the early 2000s. Practical implications of these results are presented in this paper, but mainly suggest: (i) the need to learn from past NDP best practices and contextualise them to the current complexion of the country; (ii) formulation of a handbook of implementation for climate change as an accompanying volume to the NDPs; (iii) importance of determining the climate change-industrial development trade-off; (iv) harnessing the dual correlational effect of international stimuli and domestic political forces on climate change inclusion in NDPs; (v) use of domestically-defined climate change mainstreaming and policy formulation tools; and (vi) adoption of a holistic climate change performance indicator methodology for formulating climate change related KPIs.